2019
DOI: 10.5271/sjweh.3803
|View full text |Cite
|
Sign up to set email alerts
|

Associations between shift type, sleep, mood, and diet in a group of shift working nurses

Abstract: Associations between shift type, sleep, mood, and diet in a group of shift working nurses by Heath G, Dorrian J, Coates A Among shift working nurses, night shift, more than afternoon or morning shift, was associated with mood disturbance, increased energy intake, and increased proportion of carbohydrates. Reduced sleep efficiency was also associated with higher carbohydrate intake. Results highlight the importance of examining changes across different shifts in a schedule in the context of gender and mood, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 36 publications
(54 reference statements)
4
41
0
5
Order By: Relevance
“…In line with our finding, Heath et al (23) found that higher levels of stress are associated with a higher energy intake. Under stressful conditions, humans desire palatable foods that are energy dense (24), specially elevated eating of high-sugar, high-fat foods and processed foods (25)(26)(27)(28) and a decrease in consumption of main meals, fruits and vegetables (26,28,29).…”
Section: Discussionsupporting
confidence: 93%
“…In line with our finding, Heath et al (23) found that higher levels of stress are associated with a higher energy intake. Under stressful conditions, humans desire palatable foods that are energy dense (24), specially elevated eating of high-sugar, high-fat foods and processed foods (25)(26)(27)(28) and a decrease in consumption of main meals, fruits and vegetables (26,28,29).…”
Section: Discussionsupporting
confidence: 93%
“…In line with our findings, Heath et al (27) found that higher levels of stress are associated with higher energy intake. Under stressful conditions, humans desire palatable foods that are energy-dense (28), especially elevated eating of high-sugar, high-fat foods and processed foods (29)(30)(31)(32) and a decrease in consumption of main meals, fruits, and vegetables (30,32,33).…”
Section: Discussionsupporting
confidence: 93%
“…In line with our findings, Heath et al [27], in a study on shift working nurses [N = 52; 46 female; age: 39.8 ± 12.4 years], found that higher levels of stress are associated with higher energy intake. Under stressful conditions, humans desire palatable foods that are energy-dense [28], especially elevated eating of highsugar, high-fat foods and processed foods [29][30][31][32] and a decrease in consumption of main meals, fruits, and vegetables [30,32,33].…”
Section: Discussionsupporting
confidence: 92%